Evaluasi Kekuatan Struktur Atas Pada Gedung Gas Negara Fakultas Teknik Unmer Madiun Akibat Kemiringan Bangunan - Wildan Muzakky; Seno Aji; Rendi Gusta Wibowo (LPPM Universitas Merdeka Madiun, 2021)
In a building, the beams and roof frame rest on the upright standing columns of each column is a very important technical factor before the blocks and roof frame are installed. Although a column does not stand vertically, it is a serious problem that will occur in terms of construction, it should be avoided. If the angle value of deviation in the column is outside tolerance, causing difficulties in the installation of construction. The peak of the column that has shifted from its position resulted in a tilted roof frame. This measurement uses an upfront cutting method. While on the upfront cropping method use the center of the column as the target point. Thus this research has proven that the method of cutting the surface is not only more flexible, but also more useful to control the firmness of the column on building construction work. Evaluation of the strength of the upper structure of the building at the time of tilting that can be seen from the repetition of.